Prevalence and Degree of Endoparasite Infection in Kuniran Fish (Upeneus spp.) in Pekalongan Regency - Ashari Fahrurrozi; Linayati Linayati; Wijianto Wijianto (Fakultas Perikanan dan Kelautan, Universitas Riau, 2023)
Pekalongan Regency is one of the coastal areas producing consumption fish with one species of kuniran fish (Upeneus spp). However, its production is decreasing due to growth disturbance, one of which is caused by parasitic infection. Information regarding the existence of parasites in kuniran fish is still limited. The research was conducted at the Pekalongan University Biology Laboratory from November 7 to November 30, 2022. This research aimed to discover the types of parasites that infect kuniran fish in Pekalongan Regency. The parasite's prevalence rate and degree of infection were also analyzed descriptively. The research was carried out using a sample of 36 fish. Fish were grouped into three groups, namely group I (23.3 ±1.2 cm), group II (18.5 ±0.9 cm), and group III (14.3 ±0.4 cm). The parasite results obtained from the endoparasite group, namely the Procamallanus sp. and Camallanus sp. with the highest parasite prevalence value found in group III with a size of 14.3 ± 0.4 cm both Procamallanus sp. value of 33.3% and Camallanus sp. with a discount of 50%. In addition, the degree of infection in both parasites and fish groups showed a low category.